Reducing mortality from hip fractures: a systematic quality improvement programme. Issue 1 (19th September 2014) - Lisk, Radcliffe; Yeong, Keefai
Abstract: Hip fracture is one of the most serious consequences of falls in the elderly, with a mortality of 10% at one month and 30% at one year. Elderly patients with hip fractures have complex medical, surgical, and rehabilitation needs, and a well-coordinated multidisciplinary team approach is essential for the best outcome. The model of best practice for hip fracture care is set out in the Orthopaedic Blue Book and is incentivised by the best practice tariff. In 2009 to 2010, only 39.6% of our patients were being operated on within 36 hours, 19% achieved best practice tariff [1], and mortality was 7.8%. We were ranked as one of the worst hospitals to achieve best practice tariff [1] and our mortality was average. The orthogeriatrics team at Ashford & St Peter's NHS Trust (SPH) was implemented in 2010. Through a system redesign, regular governance meetings, audits and quality improvement projects, we have managed to improve care for our patients and reduce mortality. Over the last three years we have successfully achieved best care for our hip fracture patients, demonstrating a steady improvement in our attainment of the best practice tariff and a reduction in mortality to 5.3% in 2013, which ranks us amongst the best trusts nationally.